Normative reference values for handgrip strength, shoulder and ankle range of motion and upper-limb and lower limb stability for 137 youth judokas of both sexes - Madaleno, F. O.; Verhagen, E.; Ferreira, T. V.; Ribeiro, T.; Ocarino, J. M.; Resende, R. A. (Journal of Science and Medicine in Sport, 2021)
To provide reference values for handgrip strength, shoulder and ankle range of motion (ROM) and upper-limb and lower limb stability for youth judokas of both sexes and investigate the effects of sex and side dominance. Design: Cross-sectional. Methods: A total of 137 youth judokas from under-18 ( n = 60) and under-21 ( n = 77) categories of both sexes were assessed. Handgrip strength was assessed using a Jamar dynamometer, ankle ROM was measured by lunge test, shoulder ROM was assessed by an inclinometer and upper-limb and lower limb stability were assessed by the Closed Kinetic Chain Upper Extremity Stability Test and by the Modified Star Excursion Balance Test (mSEBT). Results: In both categories, males had greater handgrip strength. In the under-18 category, the dominant side had greater handgrip strength, the non-dominant side of females had smaller shoulder external rotation ROM than the dominant side and also than both sides of males, and females had greater shoulder IR ROM. In the under-21 category, the dominant side of females had greater ankle dorsiflexion ROM than the dominant side of males, the dominant sides and females had greater shoulder ER ROM, and males had better performance in the mSEBT. Conclusions: This study provided reference values for handgrip strength, shoulder and ankle ROM, upper and lower limb stability for youth judokas, which can be used to guide assessment during preseason. Sex influenced on shoulder ER and IR ROM, handgrip strength and lower limb stability. In addition, side dominance influenced on shoulder ER ROM and on handgrip strength.